Gamifying Education: Evaluating the Role of 'Corner' Video Game in Improving Conceptual Understanding and Learning Interest - Laswadi; Handican, Rhomiy; Arnawa, I Made; Asmar, Ali (Universitas Pendidikan Ganesha, 2024)
The need for innovative approaches in mathematics learning has become increasingly urgent to address the challenges of conceptual understanding and foster sustainable learning interest among students. This study aims to evaluate the effectiveness of the educational video game